FROM CONFLICT TO CONSENSUS: ASSESSING THE NEXUS BETWEEN MEDIATION AND COMMUNAL PEACE IN BENUE STATE, NIGERIA - Adom, Amasekaven; Ugal, David Betelwhobel (African Journal of Social and Behavioural Sciences, 2025)
Mediation is a traditional mechanism considered helpful in maintaining communal peace across the globe. It was used in former times to resolve conflict among individuals and communities, but the emergence of modernization has affected its use. Yet, it is still considered helpful in achieving communal peace. Despite the emergence of modern methods of resolving conflict, it has remained endemic in society, especially in Nigeria and Benue State. Mediation is considered part of the people’s culture and hence was acceptable. The study undertook to assess how mediation engendered communal peace in Benue State. It investigates the use of mediation in resolving communal conflict. The literature was reviewed in line with the study’s objective and was anchored on the Social Control theory. A cross-sectional research design was adopted. A total of 1128 respondents participated in the study and were selected using multiple-stage sampling techniques. A structured questionnaire and in-depth interview guide were used to collect both quantitative and qualitative data, which was analysed using descriptive statistics and content analysis. The hypothesis for the study was tested using the Pearson r statistical tool. The findings revealed deliberation by neutral third parties as an effective way of mediating and resolving communal conflicts. Test of hypothesis showed a significant relationship among the variables. The study recommends support for policies that recognize and integrate traditional mediation practices into the broader framework of conflict resolution and encouragement of traditional leaders to uphold peace, thereby promoting harmonious coexistence among diverse communities in Benue State, Nigeria.